2013
DOI: 10.1111/efp.12037
|View full text |Cite
|
Sign up to set email alerts
|

Previously unrecorded low‐temperature Phytophthora species associated with Quercus decline in a Mediterranean forest in eastern Spain

Abstract: Oak decline has been a serious problem in Europe since the beginning of the twentieth century. In south-west Spain, Quercus ilex and Q. suber are the main affected species, and their decline has been associated with Phytophthora cinnamomi. During the last 10 years, a severe decline of Q. ilex and Q. faginea accompanied by a significant decrease in the production of acorns affecting natural regeneration was observed in the eastern part of the Iberian Peninsula. Therefore, the aim of this study was to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 30 publications
8
81
1
4
Order By: Relevance
“…This is similar to that of other possibly endemic low-temperature Phytophthora species such as P. ilicis , P. pseudosyringae , P. psychrophila, and P. quercina (Jung et al 1999, 2002, Pérez-Sierra et al 2013, Scanu et al 2014b, Scanu & Webber 2016). All four new species are homothallic, with a high oospore wall index (range 0.4–0.5) enabling them to survive both the long hot and dry summers typical of Mediterranean regions ( P. castanetorum , P. tyrrhenica, and P. vulcanica ) and cold winters in Austria ( P. tubulina ), on Mount Etna ( P. vulcanica ), and in the Gennargentu Mountain and Serra da Estrela ( P. castanetorum ).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is similar to that of other possibly endemic low-temperature Phytophthora species such as P. ilicis , P. pseudosyringae , P. psychrophila, and P. quercina (Jung et al 1999, 2002, Pérez-Sierra et al 2013, Scanu et al 2014b, Scanu & Webber 2016). All four new species are homothallic, with a high oospore wall index (range 0.4–0.5) enabling them to survive both the long hot and dry summers typical of Mediterranean regions ( P. castanetorum , P. tyrrhenica, and P. vulcanica ) and cold winters in Austria ( P. tubulina ), on Mount Etna ( P. vulcanica ), and in the Gennargentu Mountain and Serra da Estrela ( P. castanetorum ).…”
Section: Discussionsupporting
confidence: 79%
“…Phytophthora quercina is involved in decline syndromes of natural and planted Quercus stands ( Q. cerris , Q. coccinea , Q. faginea , Q. ilex , Q. palustris , Q. petraea , Q. pubescens , Q. pyrenaica , Q. robur , Q. rubra , Q. suber , and Q. vulcanica ) across Europe causing a progressive destruction of fine root systems, which predisposes affected oaks to climatic extremes and secondary pathogens and pests (Jung et al 1999, 2000, 2013, 2016, Balci & Halmschlager 2003a, b, Perez-Sierra et al 2013). Interestingly, P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, several defoliating insects species have been reported among the main mortality agents of oak forests, particularly in Northern America (see Haavik et al 2015 for a review). The pathogens associated with the oak decline in Mediterranean areas are generally recognizable as secondary biotic factors (i.e., due to opportunistic organisms that develop as a consequence of the loss in tree vigor), such as root fungi of the Armillaria and Phytophthora genera (De Sampaio et al 2013, Vettraino et al 2002, Perez-Sierra et al 2013, and stem cankers caused by Hypoxylon spp. Within these studies a large variability of symptoms is reported (i.e., foliage rarefaction and wilting, drying of branches, crown dieback, delay of spring bud burst, production of epicormic shoots, longitudinal cracks of the bark which is often detached, reduction of biomass, necrotic lesions and necrosis of absorbing roots - Fig.…”
Section: Causes and Mechanisms Leading To Oak Declinementioning
confidence: 99%
“…Other Phytophthora species, namely P. quercina, P. gonapodyides, and P. psychrophila, have been recently associated with declining Mediterranean oaks in Italy and Spain and their pathogenicity has been demonstrated on Quercus faginea, Q. ilex, and Q. suber Pérez-Sierra et al 2013;Seddaiu et al 2014).…”
Section: Root Pathogensmentioning
confidence: 99%